2020
DOI: 10.1155/2020/8890335
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Intrapulmonary Hemorrhage due to Vancomycin-Induced Thrombocytopenia: A Case Report

Abstract: Thrombocytopenia is a rare and sometimes life-threatening complication of Vancomycin. A 52-year-old male patient with acute kidney injury was treated with Vancomycin for ventilator-associated pneumonia. Three days later, his platelets decreased from 172×109/L to 3×109/L over a 36-hour period. The patient developed significant intrapulmonary bleeding leading to profound hypoxemia. Workup was negative for thrombotic thrombocytopenic purpura, disseminated intravascular coagulopathy, atypical hemolytic uremic synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Although platelet transfusions and steroids were given to the patient in this case, significant improvement in platelet count was not seen until the discontinuation of vancomycin. This finding was compared to other case reports of vancomycin-induced thrombocytopenia, and it was consistently discovered that significant platelet recovery began following vancomycin discontinuation [2,[5][6][7][8][9][10][11][12][13][14]. The normal time frame for platelet counts to return to levels greater than 150x10 3 /μL occurred between 5 and 7 days after vancomycin discontinuation.…”
Section: Discussionmentioning
confidence: 66%
“…Although platelet transfusions and steroids were given to the patient in this case, significant improvement in platelet count was not seen until the discontinuation of vancomycin. This finding was compared to other case reports of vancomycin-induced thrombocytopenia, and it was consistently discovered that significant platelet recovery began following vancomycin discontinuation [2,[5][6][7][8][9][10][11][12][13][14]. The normal time frame for platelet counts to return to levels greater than 150x10 3 /μL occurred between 5 and 7 days after vancomycin discontinuation.…”
Section: Discussionmentioning
confidence: 66%
“…In a study published in the New England Journal of Medicine , platelet-reactive antibodies of IgG, IgM, or both classes with vancomycin dependency were reported in 20% of the samples referred for vancomycin-induced thrombocytopenia testing [ 10 ]. A mean nadir platelet count of 13,600 per cubic millimeter (ranging from 1000 to 60,000) was attained after about eight days (ranging from 1 to 27 days) after vancomycin initiation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Her other medications included ondansetron, bupropion, sertraline, tamsulosin, pantoprazole, ergocalciferol, and insulin glargine. Additionally, the patient was placed on a prophylactic dose of enoxaparin while in-patient [ 10 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Since medication of vancomycin had been stopped, 18 days later, the patient’s platelets returned to normal, this is probably caused by the reduction of vancomycin clearance due to acute renal injury. It is suggested that the slow speed of drug clearance should be considered during medication for patients with renal function injury, which avoid serious consequences caused by drug accumulation ( Abdalhadi et al, 2020 ).…”
Section: Cases Of Adr Caused By Vap Antimicrobials Treatmentmentioning
confidence: 99%